Effects of Integrated Performance Assessment Modules on English Speaking Ability of Thai EFL Undergraduate Students - Plengkham, Benjawan; Wasanasomsithi, Punchalee (LEARN Journal: Language Education and Acquisition Research Network, 2023)
Integrating assessment into speaking instruction has been a challenge for English language instructors. The Integrated Performance Assessment (IPA), proposed by the American Council on the Teaching of Foreign Languages (ACTFL) (Adair-Hauck et al., 2015), is an assessment protocol featuring three modes of communication: interpretive, interpersonal, and presentational, to reinforce second and foreign language learning. This present mixed-method research aimed to investigate the effects of the IPA modules on Thai EFL undergraduate students’ speaking ability. Three IPA modules were taught over the course of nine weeks to 33 Thai EFL undergraduate students enrolled in an English speaking course, and the students’ performance was assessed using an adapted IPA rubric. The research instruments included a pretest, a posttest, unit tests, an IPA opinion questionnaire, and a semi-structured interview protocol. The findings indicated that the implementation of three IPA modules had a positive effect on students’ speaking ability as evidenced by the posttest results. In addition, the findings obtained from the IPA opinion questionnaire and the semi-structured interview protocol yielded further evidence of positive effects of the IPA, particularly on students’ perceived speaking improvement. Based on the study findings, it is suggested that the three IPA modules can be used as an instructional and assessment model to promote students’ speaking ability as well as to elicit insights into how English language teaching and assessment can be seamlessly integrated.